Peran Manajemen Sekolah dalam Meningkatkan Prestasi Sekolah (Studi kasus pada SD Pertiwi Abhilasa) - Ni Luh Man Eristia; I Made Awanita; I Ketut Lila Murti (Sekolah Tinggi Agama Hindu Dharma Nusantara Jakarta, 2020)
The progress of the school is very dependent on the role of the principal in leading the school, in addition there is the role of a teacher in assisting the headmaster in advancing the quality of education in schools and other collaborative school residents to help develop academic quality and improve the quality of the school so that it still exists and is able to compete with the school Another and the most important thing is to collaborate with students 'parents to develop their students' potential.From this background the authors are interested in conducting research by taking the title of the thesis